1998
DOI: 10.1029/98ja01954
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic discharge in Martian dust storms

Abstract: Abstract. Although the Martian atmosphere does not satisfy general requirements for lightning generation, there is a possibility of electrical discharge in the case of strong surface winds and a resulting extremely large dust mass loading in the course of large dust storms occurring on this planet. On Earth, negative potential gradients of many thousands of volts per meter have been measured during dust storms when winds are sufficiently strong. However, owing to a lower pressure in the Martian atmosphere, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
166
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(174 citation statements)
references
References 36 publications
7
166
1
Order By: Relevance
“…Even if no electric field has been recorded yet on Mars (ExoMars 2016 will carry an electric field measurement experiment described in Déprez et al 2015), there are several possible physical phenomena that could generate one, ranging from electrostatic charging to possible thunderstorms-see Melnik and Parrot (1998). Among these processes, the saltation process and the transport of wind-blown sand, as well as dust storms and dust devils can produce local electric fields at the surface of Mars, see Kok and Renno (2008).…”
Section: A4 Electric Field Impactmentioning
confidence: 99%
“…Even if no electric field has been recorded yet on Mars (ExoMars 2016 will carry an electric field measurement experiment described in Déprez et al 2015), there are several possible physical phenomena that could generate one, ranging from electrostatic charging to possible thunderstorms-see Melnik and Parrot (1998). Among these processes, the saltation process and the transport of wind-blown sand, as well as dust storms and dust devils can produce local electric fields at the surface of Mars, see Kok and Renno (2008).…”
Section: A4 Electric Field Impactmentioning
confidence: 99%
“…Recent numerical and analytical studies show that the micro-electro-aerodynamical system of a dust devil is an efficient giant electric generator that may trigger Martian electrical discharges and radio emissions Parrot, 1998, 1999;Farrell et al, , 2003. Experimental evidence in a Martian-like lab environment has shown the possibility of electric discharges of Martian dust storms [Eden and Vonnegut, 1973], and theoretical and modeling studies have indicated that under some conditions, discharging may occur [Melnik and Parrot, 1998;Farrell et al, 2003]. However, many critical issues, such as under what conditions can the field reach breakdown values and whether charge and electric field growth will be saturated before reaching the breakdown, have not been systematically addressed.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Dust particles are electrified in a dust devil when they collide with each other as a result of differences in sizes and contact potentials between compositionally distinct materials [Melnik and Parrot, 1998;Desch and Cuzzi, 2000]. When two particles of similar composition collide, the smaller grain tends to be negatively charged, and the larger grain obtains an equal but opposite charge.…”
Section: Introductionmentioning
confidence: 99%
“…The size-dependence of particle triboelectrification is observed in both natural phenomena [10,65] and industrial processes [11,66], which gives it priority in research fields and for which many modeling studies have been conducted [9,67,68].…”
Section: Particle Sizementioning
confidence: 99%